Grief‐related beliefs in shidu parents with and without prolonged grief disorder: Psychometric properties of a Chinese version of the Typical Beliefs Questionnaire. (19th August 2021) - Xu, Xin; Wen, Jun; Skritskaya, Natalia A.; Zou, Xinyan; Mauro, Christine; Wang, Jianping; Shear, M. Katherine
Abstract: The Typical Beliefs Questionnaire (TBQ) assesses common grief‐related cognitions, which demonstrated satisfactory psychometric properties in a treatment‐seeking sample with prolonged grief disorder (PGD). Chinese shidu parents (bereaved parents over the age of 49 who have lost their only child) are at a high risk of PGD. The current study aimed to examine psychometric properties of the Chinese version of the TBQ (TBQ‐C) in a community sample of shidu parents with and without PGD, to compare this to the original validation clinical sample in the United States bereaved of any close relationship and to consider its use as a clinical tool. We examined the rate of positive endorsement, factor structure, internal consistency and validity of the TBQ‐C in 310 community‐based shidu parents (including 102 who met the criteria for PGD). Results showed that the rate of positive endorsement for each item ranged from 7.2% to 48.6% among non‐PGD participants and from 20.6% to 92.2% among PGD participants. Confirmatory factor analysis indicated that the original five‐factor structure fit both the non‐PGD and PGD shidu parents. The TBQ‐C showed acceptable internal consistency and satisfactory convergent and concurrent validity in both groups. It had good discriminant validity and can be helpful in distinguishing shidu parents with and without PGD. The TBQ‐C can be used to investigate common grief‐related beliefs that may be problematic for both shidu parents with and without PGD.